Study on the influencing factors of spontaneous wettability transition behaviour on metallic-based surfaces. (June 2022) - Wang, Jie; Wu, Mengjuan; Hou, Xianghui
Abstract: Hydrophobic surfaces and coatings have attracted more and more interest in recent years due to their broad applications in diverse areas. In many cases, a metallic surface would demonstrate a reversible wettability from hydrophilic state to hydrophobic state spontaneously. However, the wetting behavior and hydrophobic mechanism of metallic surfaces are far from clear. In this work, 304 stainless steel (SS) surface and Ni–Cu–P coatings have been chosen to investigate the intrinsic mechanism of the surface wettability transition with the help of X-ray photoelectron spectroscopy (XPS) and ambient air/vacuum storage treatment. The surface topographies, wetting behaviors and surface chemistry were studied systemically. The results showed that water contact angle (WCA) variation of the as-prepared surfaces changing from hydrophilic state to hydrophobic state is largely associated with the specific surface area. The recovery of water repellency is related to a time constant which mainly depends on micro-scale surface convolution or surface roughness. Rougher surface tends to accelerate the surface adsorption of airborne hydrocarbon species in the ambient atmosphere, leading to a more intensive WCA increase. The study provides a generic theoretical justification for relevant time-dependent wettability studies. Highlights: The spontaneous wettability transition behaviour on metallic-based surfaces with different surface roughness were investigated in detail. The variations of surface hydrocarbon adsorption and lattice oxygen groups change were responsible for the wettability transition. A model for the exponential WCA recovery based on the empirical evidences of WCA recovery process has been proposed. The surface roughness could affect the specific surface area and the characteristic timescale of the whole WCA recovery process.